Reviews and responses for A First Look at Leveraging the Automatic Dependent Surveillance-Contract Protocol for Open Aviation Research - Arts, Emy; Lovell, David; Xapelli, Marc; Lüscher, Tobias; Tresoldi, Giorgio; Lenders, Vincent; Strohmeier, Martin (Journal of Open Aviation Science, 2023)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2023.7229